2011
DOI: 10.1007/s11605-010-1330-8
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Outcome Following Surgery in Colonic Perforation: An Institution’s Experience Over 6 Years

Abstract: Surgery for colonic perforation is associated with high morbidity and mortality rates. Short-term outcome is determined by ASA score and severity of peritonitis. A lower haematocrit level must alert the possibility of malignancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
18
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 38 publications
6
18
0
Order By: Relevance
“…Torer et al and Tan et al identified possible prognostic relevance for the MPI in retrospective cohorts with patients with secondary peritonitis due to postoperative complications and community acquired perforations of small bowel and colon [17-20]. However, quantification of or changes in organ failure does not seem to differentiate between ongoing organ failure due to abdominal sepsis despite source control of the initial causative focus and ongoing abdominal infection.…”
Section: Discussionmentioning
confidence: 99%
“…Torer et al and Tan et al identified possible prognostic relevance for the MPI in retrospective cohorts with patients with secondary peritonitis due to postoperative complications and community acquired perforations of small bowel and colon [17-20]. However, quantification of or changes in organ failure does not seem to differentiate between ongoing organ failure due to abdominal sepsis despite source control of the initial causative focus and ongoing abdominal infection.…”
Section: Discussionmentioning
confidence: 99%
“…In our study we want to demonstrate efficacy of MPI and the possibility to consider older age an independent prognostic factor, analysing a perforative peritonitis population with high percentage of older patients (16)(17)(18).…”
mentioning
confidence: 99%
“…We found that the overall incidence of intestinal perforation was low, at 4.6 events per 1,000 person years, while nearly half of the patients (42%) who experienced an intestinal perforation died within 30 days. The overall in-hospital mortality rates of intestinal perforation were 10%–20% in the general population (16). We also tested whether the incidence of intestinal perforation changed after market introduction of sevelamer hydrochloride in late 1998, a hypothesis that was motivated by safety concerns that had previously been weighed by the US FDA.…”
Section: Discussionmentioning
confidence: 99%
“…Intestinal perforation is rare in the general population, but carries a high risk of mortality (16). We recently observed that patients undergoing dialysis had high rates of acute nonvariceal gastrointestinal bleeding, which was up to 2 orders of magnitude higher than in the nondialysis population (7).…”
Section: Introductionmentioning
confidence: 99%